Building a comprehensive phylogenetic framework in disease ecology. Issue 6 (June 2022) - Filion, Antoine; Doherty, Jean-François; Poulin, Robert; Godfrey, Stephanie S.
Abstract : Disease spillover can have dramatic consequences in multispecies systems, potentially leading to the emergence of zoonoses. To better understand disease emergence patterns, an approach encompassing species relatedness metrics is needed. We show that integrating phylogenetic information in disease ecology is still lagging, and we highlight potential solutions to solve this problem.